2021
DOI: 10.1155/2021/6643171
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Alleviates Hypoxia‐Induced Synaptic Loss and Cognitive Impairment via Inhibition of Microglial NOX2 Activation in the Hippocampus of Neonatal Rats

Abstract: Background. Perinatal hypoxia is a universal cause of death and neurological deficits in neonates worldwide. Activation of microglial NADPH oxidase 2 (NOX2) leads to oxidative stress and neuroinflammation, which may contribute to hypoxic damage in the developing brain. Dexmedetomidine has been reported to exert potent neuroprotection in several neurological diseases, but the mechanism remains unclear. We investigated whether dexmedetomidine acts through microglial NOX2 to reduce neonatal hypoxic brain damage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Chen et al ( 45 ) aimed to further clarify the mechanisms and report that DEX protects against MTX-induced cognitive impairment by inhibiting neuronal toxicity and inflammation. In hypoxia-activated BV2 microglia and neonatal rats subjected to hypoxia, DEX decreases hippocampal synaptic loss and neuronal damage and the potential mechanisms may be that DEX prevents hypoxia-induced microglial NOX2 activation and then inhibits oxidative stress and the neuroinflammatory response ( 46 ). Mei et al ( 47 ) also report that DEX alleviates BBB disruption, learning and memory impairments, systemic inflammation and neuroinflammation in a cecal ligation and puncture (CLP)-induced septic model.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 45 ) aimed to further clarify the mechanisms and report that DEX protects against MTX-induced cognitive impairment by inhibiting neuronal toxicity and inflammation. In hypoxia-activated BV2 microglia and neonatal rats subjected to hypoxia, DEX decreases hippocampal synaptic loss and neuronal damage and the potential mechanisms may be that DEX prevents hypoxia-induced microglial NOX2 activation and then inhibits oxidative stress and the neuroinflammatory response ( 46 ). Mei et al ( 47 ) also report that DEX alleviates BBB disruption, learning and memory impairments, systemic inflammation and neuroinflammation in a cecal ligation and puncture (CLP)-induced septic model.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is known that intracellular ROS was produced through multiple enzymes mainly composed of, but not limited to, NADPH oxidase, nitric oxidase, amine oxidase, oxalate oxidase, and peroxidases. Although it was reported that hypoxia may increase ROS production in microglia by inducing NADPH oxidase 2 [ 56 ], and it was shown that hypoxia induced ROS generation via NADPH oxidase 4 in mouse hippocampus [ 57 ], highly implying the role of NADPH oxidase, we did not investigate the exact pathway responsible for ROS production in the current study. Second, intracellular oxidative status depends on the balance between the generation and removal of ROS, which may involve superoxide dismutases, catalase, and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 95%
“…The Morris water maze (MWM) test was performed to test the cognitive function of diabetic and nondiabetic rats on days 3, 7, and 14 after surgery as previously described. 33 The maze (150 cm in diameter and 50 cm in depth) was divided into four quadrants, and a platform (12 cm in diameter) was submerged 1 cm below the water line in one quadrant of the pool. In the MWM test, a video camera connected to the computer running the tracking software (Panlab) was placed above the center of the maze to record and analyze the rats' movements.…”
Section: Morris Water Maze Testmentioning
confidence: 99%